KONSEP WAKTU PADA SISTEM TIME VALUE OF MONEY DAN ECONOMIC VALUE OF TIME; PERSPEKTIF ISLAM - Ridan Muhtadi; Moh. Fudholi; Mohsi Mohsi; Fahmi as-Sulthoni; Zainurrafiqi Zainurrafiqi (LP2M IAI Miftahul Ulum Pamekasan, 2017)
Money becomes a business commodity for profit without regard to normative realities and human ethics. The concept of time value of money remains a subject of debate among Muslim scholars because it is considered to provide justification for usury. In conventional economic practice the concept of time value of money is known, which is a concept of adopting a biological model that results in the value of money today being more valuable than in the future. At first glance, it appears that Islam sets a double standard by looking at time differently in two this case: on the one hand, Islam makes it part of the price in the case of deferred sales but eliminates any value in terms of loans. We believe that this issue requires a more comprehensive consideration to know, beyond this apparent duality, the true perception of Islam about the role of time economy.